Transvaginal ultrasound in deep endometriosis: pictorial essay - Oliveira,Jorge Gilmar Amaral de (2019)
Abstract Endometriosis is characterized by the presence of endometrial tissue outside the uterus. When endometrial implants penetrate more than 5 mm into the peritoneum, the condition is referred to as deep pelvic endometriosis. Although laparoscopy is the gold standard test to establish a diagnosis of deep endometriosis, transvaginal ultrasound represents an alternative that can contribute to detection of the disease, because it is an accessible, low-cost, noninvasive examination that allows preoperative planning in cases requiring surgical treatment. However, in clinical practice, transvaginal ultrasound is still not widely used as the first-line examination in suspected cases of endometriosis. This essay describes the findings of deep endometriosis on transvaginal ultrasound, in order to disseminate knowledge of the utility of the technique for the diagnosis of this disease.